A New Notion of Inner Product in A Subspace of n-Normed Spaces - Nur, Muh; Idris, Mochammad (IndoMS, 2023)
Given an n-normed space X for n>= 2, we investigate the completness of Y (as subspace of X) respect to a new norm that corresponds this new inner product on Y. Moreover, we discuss the angle between two subspaces in Y.